2022
DOI: 10.1007/s00259-022-05974-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual radiosensitivity reflected by γ-H2AX and 53BP1 foci predicts outcome in PSMA-targeted radioligand therapy

Abstract: Purpose γ-H2AX and 53BP1 are fundamental for cellular DNA damage response (DDR) after radiation exposure and are linked to cell repair, arrest, or apoptosis. We aimed to evaluate whether DDR-markers in peripheral blood lymphocytes (PBLs) may have predictive potential for outcome in metastatic castration-resistant prostate cancer (mCRPC) patients receiving [177Lu]Lu-prostate-specific membrane antigen (PSMA) radioligand therapy (RLT). Methods We prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Widjaja et al . 48 evaluated DNA damage repair (DDR) markers in peripheral blood lymphocytes (PBLs) to assess if these markers could predict outcome of 177 Lu-PSMA-RLT; this preliminary study showed that low baseline DDR markers in PBLs trended toward poor treatment outcomes. Future studies ideally will be embedded into phase III trials with clinically meaningful endpoints.…”
Section: Predicting Outcomes With Psma-rltmentioning
confidence: 99%
“…Widjaja et al . 48 evaluated DNA damage repair (DDR) markers in peripheral blood lymphocytes (PBLs) to assess if these markers could predict outcome of 177 Lu-PSMA-RLT; this preliminary study showed that low baseline DDR markers in PBLs trended toward poor treatment outcomes. Future studies ideally will be embedded into phase III trials with clinically meaningful endpoints.…”
Section: Predicting Outcomes With Psma-rltmentioning
confidence: 99%
“…Therefore, to find out the downstream molecular markers involved in cell death, a DNA damage marker and a cell death marker were evaluated. H2AX phosphorylation (γH2AX) is a well-known marker of an early cellular response to DNA double-strand breaks, and Caspase 3 is a key molecule involved in cell death ( Chen et al, 2022 ; Widjaja et al, 2023 ). In this study, western blot analysis showed that Bi-212-MAA treatment induced H2AX phosphorylation in 4T1-treated cells ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, no change was seen in markers of radioresistance, specifically proteins involved in cell cycle checkpoint control. It is known that increased radiation dose can lead to cell cycle arrest and cell survival, making it critical to find a sensitive dose ( Chan Wah Hak et al, 2022 ; Chen et al, 2022 ; Widjaja et al, 2023 ). Alpha (α)-particle therapy works through direct double-stranded DNA breaks, thus leaving the cell with very few options for resistance and survival.…”
Section: Discussionmentioning
confidence: 99%
“…43 A diminished γH2AX response has been associated with increased radiosensitivity or chemosensitivity and poor outcome, so the identification of non-responders' patients may contribute to optimizing and personalizing cancer treatments. 44,45 Another study found no predictive utility for γH2AX and 53BP1 foci determinations regarding the radiotherapy outco-me. 33 The measurement of γH2AX and 53BP1 foci in PBL of patients receiving radioligand therapy may contribute to predicting patients with gastroenteropancreatic neuroendocrine tumors at high risk of early progression.…”
Section: Discussionmentioning
confidence: 99%